Against the Carceral Logics of Schools: A Critical Ethnographic Study of Restorative Justice and Politicized Caring in a Black School - Rowhea Elmesky; Olivia Marcucci (SAGE Publishing, 2024)
Restorative justice has the potential to re-frame schools as caring and politically conscious educational spaces. As it moves to the mainstream, however, it risks being co-opted by the carceral logics that undergird the schooling of Black students in the United States. This ethnographic analysis interrogates how restorative justice provides opportunity to politicize care within the boys mentoring group at one predominantly Black high school. Specifically, the adults used the restorative circle to (1) express verbal and physical affection and (2) evoke and acknowledge shared emotions, while also (3) recognizing the positionalities and lived experiences of the Black boys in the circle and (4) co-constructing socioemotional and cognitive-behavioral tools to navigate the structures that surround them. We argue that this politicized caring is crucial to ensuring restorative practices optimize their anti-carceral potential.